2016
DOI: 10.1155/2016/6219761
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study of the Clavicles in a Chinese Population

Abstract: Background. A reemergence of interest in clavicle anatomy was prompted because of the advocacy for operative treatment of midshaft clavicle fractures. Several anatomical studies of the clavicle have been performed in western population. However, there was no anatomical study of clavicle in Chinese population. Patients and Methods. 52 patients were included in the present study. Three-dimensional reconstructions of the clavicles were generated. The length of the clavicle, the widths and thicknesses of the clavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
4
2
Order By: Relevance
“…The Asian specimens (with CL 143.7 ± 9.1 mm) in this study were all from Japan. When comparing the distribution of the Asian mean CLs in this study with the results of Qiu et al 18 on 104 Chinese clavicles (mean, 144.2 ± 12.0), no statistical difference was found in the overall distribution ( P = .703, summarized t -test). In this study, the CL was shown to be significantly longer in male specimens (148.4 ± 9.1 mm) than in females (136.0 ± 8.3 mm).…”
Section: Discussioncontrasting
confidence: 47%
“…The Asian specimens (with CL 143.7 ± 9.1 mm) in this study were all from Japan. When comparing the distribution of the Asian mean CLs in this study with the results of Qiu et al 18 on 104 Chinese clavicles (mean, 144.2 ± 12.0), no statistical difference was found in the overall distribution ( P = .703, summarized t -test). In this study, the CL was shown to be significantly longer in male specimens (148.4 ± 9.1 mm) than in females (136.0 ± 8.3 mm).…”
Section: Discussioncontrasting
confidence: 47%
“…The total length of a fixation plate is 70 mm, the hook's depth is 12 mm. the lateral and the middle segments of the clavicle intersect at the angle of 150° (Qiu et al, 2016). A model of a fixation plate is provided in Figure 1 below.…”
Section: Methodsmentioning
confidence: 99%
“…The lateral half of the later has a longitudinal subclavian groove (Ishwarkumar et al, 2016). Human clavicle fractures account for 3%-10% of all fractures and for 35-44% of fractures about the shoulder (Qiu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%